Derivación de valores económicas de la producción de leche de bovinos en la parroquia Belisario Quevedo utilizando funciones de beneficio. - Burbano Espín, Kevin Santiago (2022)
Determine selection criteria based on agriculture economic flows units is essential to determinate important expenses that hinder the profitability production. The objective of this investigation is to derive economic values of bovine milk production in Belisario Quevedo parish using profit functions. Dairy farms were evaluated through household surveys of their owners. Animals were measured in parameters such as daily gain weight, calving interval, open days, longevity, milk density and mammary gland health with Californian Mastitis Test. In addition, animal stocking rate of paddocks was calculated by taking 10-15 samples of forage; Information about economic flows (income and expenses) was collected, with all that information, selection criteria was derived to solve and resolve the problems found in the productive units. The dairy producers have a median of 0.37 hectares, with poor pasture management and animal overloading in 70% of cases, producing an average approximately 5.7 kg milk /hectares/cow; this increased production costs, especially complementary foods and paddock leases. The 40.3% of the sample are producer cows, while 79.9% corresponds to bovine females from different ages. Animals comparing age ranges, it is observed the most is 6 – 18 months old and none of them is older than 6 years, which shows a decreasing productive life. 43% of the sample are external animals as a result to high costs, mortality and morbidity index, so they decide not to breed calfs and instead buy pregnant cows, being the breed of choice Holstein Friesian in 77.3%. Production costs of $800 and $300 in feed and paddocks are observed, generating economic losses up to $300 per month. The main selection criterion determined fertility, well it is considerated an economic indicator; as a consequence, to its low heritability index, it needs more generations to establish the allelic sequences in a population. Profitability was not obtained in 70% of the producers. Selections criteria for fertility, daily gain weight and milk density were determined.